Synthesis of ε-oxo acids by photostimulated reactions of 2-(2-iodophenyl)acetate ion with carbanions by the SRN1 mechanism. Synthesis of novel 3-benzazepin-2-ones - Guastavino, Javier Fernando (2011)
The synthesis of 3-benzazepin-2-ones using commercially available 2-(2-iodophenyl)acetic acid as starting material is described. The synthetic strategy involves the SRN1 substitution reaction in DMSO as solvent under photoinitiation, using ketone enolate ions as nucleophiles to obtain ε-oxo acids, followed by a condensation reaction of ε-oxo acids with ammonium acetate in glacial acetic acid to produce novel 3-benzazepin-2-ones. The target compounds are afforded in regular to good yields and the factors governing the distribution of substitution products are discussed. © ARKAT-USA, Inc.